Endomycopsis apis, sp. nov., Fungus, parásito de las abejas Apis mellifica L. en Venezuela. - stejskal, M (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Endomycopsis apis sp. nov., Fungus, fam Endomycetaceae, subfam. Sacchatomycetoideae, tribe Endomycopseae, genus Endomycopsis, parasite of the hemolympb of the adult honey bee Apis mellifica L., found in Venezuela, has a sexual and asexual reproduction. The sexual reproduction the asci are formed at the ends of diploid hyphae or are intercalary, with parthenogenetic evolution, form 2 to 4 ascospores of different sex. From the fertilized ascospores diploid hyphae develop, with oval segments, separated by septa and branched. From these segments blastospores are produced.